2020
DOI: 10.4274/tpd.galenos.2019.6137
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Epidemiology of Cutaneous Leishmaniasis in Northeastern Iran

Abstract: Khorozan-Razavi eyaleti, Kuzey Doğu İran'da yer alan, anthroponotik kutanöz leishmaniasis (AKL'nin sebep olduğu Leishmania tropica) ve zoonotik kutanöz leishmaniasis (ZKL'ye sebep olan Leishmania major) için endemik bir bölge niteliğindedir. Bu çalışmada klinik önem bakımından bazı şehirler AKL olarak nitelendirilmesine karşılık bazı şehirler ZKL olarak tanımlanmıştır. Bu araştırma, kutanöz leishmaniasis (KL) olarak teşhis edilmiş hastalardan elde edilen örneklerin direkt mikroskobik bakıyla teşhisleri ile ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The results obtained showed that the Leishmania species present in all 100 samples was L. major , which is not surprising. In previous work at these regions, L. major was the dominant causative agent of leishmaniasis ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained showed that the Leishmania species present in all 100 samples was L. major , which is not surprising. In previous work at these regions, L. major was the dominant causative agent of leishmaniasis ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rodents are the main reservoir hosts, and some of the more endemic species include Rhombomys (R.) opimus, Meriones libycus, Ta t e ra (T. ) indica, and Meriones hurrianae. Phlebotomus papatasi transmits L. major, whereas Phlebotomus sergenti transmits L. tropica [70,[77][78][79]. ACL and ZCL are present, L. tropica and L. major are endemic in Saudi Arabia, and CL is declining with fewer instances being reported [80][81][82][83].…”
Section: New World Cutaneous Leishmaniasismentioning
confidence: 99%
“…CL is endemic in 87 countries globally, with an estimated 500,000 to 1,000,000 new cases reported each year [36] . The majority of cases occurred in two regions (Eastern Mediterranean Region and America Region), mostly in seven countries: Afghanistan [51,52] , Algeria [53,54] , Brazil [55,56] , Iran [57,58] , Iraq [59,60] , Pakistan [61,62] and Syria [63] . The transmission cycle of the infection involves various species of leishmania, some of which are zoonotic, with reservoir hosts that can vary between domestic and wild mammals.…”
Section: Overview Of Cutaneous Leishmaniasismentioning
confidence: 99%